Assessment of the Viability of Mycobacterium Leprae by 16S rRNA Using Different Methods for Rapid Extraction of rRNA: Evaluation of Mycobacterium leprae viability using diverse rRNA extraction techniques (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Leprosy, a chronic disease caused by Mycobacterium leprae is a general wellbeing worry in specific nations, including India. Despite the fact that the pervasiveness of the disease has fallen definitely after some time, new cases keep on happening at almost a similar rate in numerous locales. A few endemic pockets have been seen in India and somewhere else. The exact elements of infection transmission are as yet not unmistakably comprehended. Both live bacilli just as M. leprae DNA have been recognized in the dirt and water of endemic zones they potentially assume a significant job in illness transmission. Nucleotide arrangement information for bacterial 16s ribosomal RNA was utilized to distinguish oligodeoxyribonucleotide groundworks appropriate for testing the rRNA quality of mycobacteria and related life forms, with the polymerase chain response. The strategy empowered us to separate mycobacteria from other firmly related genera, and to separate among moderate and fast growing mycobacteria. Mycobacterium leprae fell inside the moderate developing gathering of mycobacteria yet there are critical contrasts between the succession of the M. leprae 16s rRNA quality and that of other moderate developing mycobacteria. These distinctions were utilized to devise a quick, non-radioactive strategy for recognizing M. leprae in contaminated tissue. This paper is designed to evaluate the viability of Mycobacterium leprae by different methods for diagnosis.